Work-related musculoskeletal disorders in home care nurses: study of the main risk factors - Carneiro, P. (2017)
BACKGROUND: Nurses are a risk group for work-related musculoskeletal disorders (WMSDs). Several studies reveal that nurses have high prevalence rates of injuries and symptoms related to WMSDs. However, many of these studies focus mostly on hospital nurses. Worldwide, few studies include home care nurses. Objective This work aimed to identify the body region most affected by musculoskeletal complaints in home care nursing, and subsequently develop a statistical model, that includes the main risk factors, to predict the risk of having musculoskeletal complaints in the identified region. Methods The research method was based on the Standardised Nordic Questionnaire applied to home care nurses working at Health Centres of northern Portugal. Univariate and multivariate models of logistic regression were used to meet the goals of this work. Results Home care nurses have a three times greater chance of having lumbar complaints than their counterparts working only at Health Centres (OR = 3.19 (p < 0.05), with a 95% confidence interval [1.256; 8.076]). A statistical model with seven variables (forearm posture; static postures; arm posture; arm supported; bed height; job satisfaction; assistive devices) was obtained to predict lumbar complaints. Conclusions The lumbar region was identified as the most affected by musculoskeletal complaints. These complaints were associated with seven factors.